Can heat-pulse sap flow measurements be used as continuous water stress indicators of citrus trees? - Ballester, Carlos; Castel, Juan R.; Testi, Luca; Intrigliolo, Diego S.; Castel, Juan R. (2017)
Transpiration of well-watered and regulated deficit irrigated (RDI) citrus trees was determined by sap flow (SF) measurements using the compensation heat-pulse method. Its potential for detection of plant water stress was evaluated in comparison with measurements of midday stem water potential (psi(stem)). The study was carried out during 2 years in two commercial groves of Clementina de Nules (CN) and Navel Lane Late (NLL). SF measurements were taken in two trees per treatment instrumented with two identical gauges per tree in NLL and two different types of gauges (type 1 shorter than type 2) in CN. The absolute SF values underestimated the tree water use. Averaged over the entire period of water restrictions, a reduction of about 50 % in water application in the RDI trees of both species decreased tree transpiration compared to the control trees only by a 15 %. Both the nocturnal-to-diurnal SF ratio and the relative transpiration were in good agreement with differences in psi(stem). Overall, results suggest that SF measurements should be preferentially used in relative terms. Sap flow sensors are useful for detecting plant water stress, but they also highlight some of the problems for accurately measuring transpiration.